Campbell biology - Urry, Lisa A.; Cain, Michael L. (Michael Lee), 1956-; Wasserman, Steven Alexander; Minorsky, Peter V.; Orr, Rebecca B.; Campbell, Neil A., 1946-2004. (New York, NY : Pearson, 2021)
"For the last three decades, Campbell Biology has been the leading college text in the biological sciences. It has been translated into 19 languages and has provided millions of students with a solid foundation in college-level biology. This success is a testament not only to Neil Campbell's original vision but also to the dedication of hundreds of reviewers (listed on pages xxviii-xxxi), who, together with editors, artists, and contributors, have shaped and inspired this work"--
Unit 1. The chemistry of life -- Unit 2. The cell -- Unit 3. Genetics -- Unit 4. Mechanisms of evolution -- Unit 5. The evolutionary history of biological diversity -- Unit 6. Plant form and function -- Unit 7. Animal form and function -- Unit 8. Ecology.
Includes bibliographical references and index.
Appendices and glossary paginated as follows: A-50, B-2, C-1, D-4, CR-10, G-35, I-52.
Keywords: Biology; Biology; Biologie; biology; Biology; Kindle etextbook collection; Textbooks